The Incentive Effect of Fiscal Equalization Transfers on Tax Policy - Thiess Büttner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2005)
A theoretical analysis considers the impact of a typical system of redistributive "fiscal equalization" transfers on the taxing effort of local jurisdictions. More specifically, it shows that the marginal contribution rate, i.e. the rate at which an increase in the tax base is reducing those transfers, might be positively associated with the local tax rate while the volume of grants received is likely to be inversely related to the tax base. These predictions are tested in an empirical analysis of the tax policy of German municipalities. In order to identify the incentive effect the analysis exploits discontinuities in the rules of the fiscal equalization system as well as policy changes. The empirical results support the existence of an incentive effect, suggesting that the high marginal contribution rates induce the municipalities to raise their business tax rates significantly.
Keywords: H71; H77; 330; Fiscal Equalization; Tax Competition; Fiscal Federalism; Incentive Effect of Taxation; Regression Discontinuity; Gemeindesteuer; Steuerwettbewerb; Finanzföderalismus; Steuerbemessung; Deutschland